Friday

October 24, 2014

October 24, 2014

Posted by **Veronica** on Friday, July 6, 2007 at 11:01am.

Using the quadratic formula solve xsquared=2/3x

x^2 - 2x/3 = 0

x = [+2/3+/-sqrt(2/3^2 - 4(1)0)]/2

**Answer this Question**

**Related Questions**

College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...

Math - Use the quadratic formula to solve each of the following quadratic ...

math-calculus - solve equation |x^2-2x-6| using quadratic formula. i not get how...

Algebra - Solve for y in terms of x . Determine if y is a function of x . If it ...

Math - how do you solve for y in the expression: x^3=y(y+3)? x^3=y^2 + 3y y^2+3y...

math - solve the quadratic equation xsquared - 2x - 3 = 0

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

algebra - using quadratic formula 3y2=6+7y 3 y^2 -7y - 6 = 0 When using the ...

math - 15t^2+7t=2 The quadratic formula tells you that the solutions are: t = [-...

Math!Please Help Me! - Solve the following quadratic by either factoring or ...